Developing authentic assessment instrument based on multiple representations to measure students' critical thinking skills - Muhammad Minan Chusni; Suherman Suherman (Universitas PGRI Kanjuruhan Malang, 2021)
The purpose of this study was to produce an instruments test used to measure students' critical thinking skills in natural science learning. This research uses a 4-D development model (define, design, develop, and disseminate) involving 118 students at the develop stage and 60 students at the disseminate stage. The instrument developed was an essay test based on multiple representations. Validity was proved by using CVI, and reliability was estimated by using the Item Response Theory. The results showed that the instrument had a very good foreign exchange value. This is reflected in the Aiken V scores on the aspects of substance, construct, language and appearance, respectively, about 1.00, 1.00, 1.00, and 1.00. According to Rasch analysis, the instruments has meet the assumption test for 14 items which is unidimensional, the local independence assumption test, and the parameter invariance assumption test. According to OUTFIT MNSQ Value, the items are fit with PCM 1-PL which functions normally in making measurements. Reliability estimated for items shows a very high consistency of measurement of 0.97 and for person shows a high consistency of measurement of 0.86. The results of the student's CTS measurement showed that the average score was 65.50, with a distribution of high, medium, and low abilities, respectively, about 16.67%, 63.33%, and 20.00%. Thus, according to these results, an authentic assessment based on multiple representations is suitable to measure students' critical thinking skills.